GP cooperative and emergency department: an exploration of patient flows. Issue 2 (5th February 2012) - Huibers, Linda; Thijssen, Wendy; Koetsenruijter, Jan; Giesen, Paul; Grol, Richard; Wensing, Michel
Abstract Rationale, aims and objectives In most countries, different health care providers are involved in emergency care. In the Netherlands, out‐of‐hours care is provided by general practitioner cooperatives (GPCs) and emergency departments (EDs). Our aim was to describe the flow of patients attending emergency care in these settings. Method A retrospective record review was performed, concerning patients who had visited a GPC or ED. Recorded information included urgency, diagnostic tests, and follow‐up contacts. Descriptive figures were determined for patient flows in GPC and ED for urgent contacts and non‐urgent contacts. Results We included 319 GPC contacts and 356 ED contacts, of which 78% were non‐urgent. The majority of GPC contacts were completed at the GPC without follow‐up; 37% of non‐urgent patients had a follow‐up contact, usually with primary care. Only 5% of non‐urgent GPC patients received diagnostic tests compared to 63% of non‐urgent ED patients (mostly X‐rays). The majority of non‐urgent ED patients (88%) had a follow‐up contact, usually at an outpatient clinic (67%). Most non‐urgent ED patients (83%) who received a diagnostic test also had an outpatient clinic follow‐up contact. Of urgent ED patients, the majority had a follow‐up contact (85%), mostly with an outpatient clinic (74%). Conclusion Although most out‐of‐hours care patients present non‐urgent health problems, at the ED they are more likely to receive diagnostic tests and follow‐up contacts. This may reflect differences in patient populations between the ED and GPC or suggest opportunities for improving efficiency of planning follow‐up contacts.